Isolation and characterization of lignin from okra (Abelmoschus esculentus) fibre and stick (Bangladesh Journal of Scientific and Industrial Research, 2015)
The okra (Abelmoschus esculentus) plant consists of bast fiber and core (stick). The bast fibre of okra plant was characterized with high ?-cellulose (56.7%) and low lignin (12.6%) and stick withlow ?-cellulose (34.3%) and high lignin (25.2%) content. Lignin was isolated from the fiber and stick by acidolytic dioxane method and characterized for elemental analysis, methoxyl analysis and FTIR and 1H-NMR spectroscopy. The C9 formulas for okra stick and fibre lignin were C9H9.61O4.63(OCH3)1.24 and C9H8.61O4.66(OCH3)1.49, respectively. Both of the lignins were of the guaiacyl-syringyl type. The bands of FT-IR spectrum at 1327 cm-1, 1122 cm-1 and 837 cm-1 associated with syringyl unit was higher in okra fibre lignin than in the okra stick lignin. The structural analysis revealed that the average numbers of proton of ?-O-4 (H? & H?) per C9 unit in okra stick and fibre lignin were 1.53 and 1.20, respectively. The ?-O-4 units in these lignins had predominately erythro stereochemistry type.Bangladesh J. Sci. Ind. Res. 50(4), 257-262, 2015